(untitled) (Research, Society and Development, 2022)
The Covid-19 pandemic generated numerous challenges, among them university training due to the suspension of face-to-face activities, due to social isolation. There were adaptations to the new reality and the virtual environment became an ally for students and educators, however, with the persistence of the pandemic moment and the need for qualified labor, the students graduating from the Physiotherapy course felt the need to enter the professional life . Thus, this article explains the process of implementing an extension study in times of pandemic and social distancing, its interactions with teaching and research, as well as the difficulties encountered and the preliminary results. This study seeks to track individuals diagnosed with Covid-19 and who required hospitalization, assess their functionality, monitor and/or refer them to specialized services. The main difficulties encountered were regarding contact with patients and the availability and training of students to carry out the assessments, either by phone call or in person. Vaccination of students made it possible to return to face-to-face activities and thus access to the covid sector, allowing the identification of the main limitations of patients and accompanying them or referring them to specialized services. Due to satisfaction with the results, the project was expanded, opening up research and evaluation in the Covid Intensive Care Unit. Thus, the project made possible the articulation of the teaching, research and extension tripod, helped in the academic training of those who completed the Physiotherapy course and involved society, supplying their needs in the current pandemic scenario, assisting in the rehabilitation after infection by SARS-CoV-2.